FLOUTING MAXIMS IN “FIVE FEET APART” MOVIE - Cut Nadira Dwiyanti; Ambalegin Ambalegin (IdeBahasa, 2022)
This study used a pragmatic study to discover the flouting of maxims in the “Five Feet Apart” movie. This descriptive qualitative research was done with observational method and non-participatory technique. Data collection was obtained from watching the “Five Feet Apart” movie by using pragmatic identity method and pragmatic competence- in equalizing technique. Then, the data were analyzed and classified based on the type of flouting of the maxims according to the theory of Grice (1989). The highest frequency was the flouting maxim of relevance with a total of 8 data. Meanwhile, the lowest frequency was found in flouting maxim of manner and quantity with each having one data. The result of this research was that the researchers found the reason why the characters in Five Feet Apart movie flouted all the maxims. The characters flouted the maxims because they wanted to change the topic, sarcasm, and cover up their feelings. The conversations in Five Feet Apart movie could still be easily understood, even though the characters in this movie flouted all the maxims. Even with the flouting maxims, the plot of this movie became more interesting.